A single-dose MCMV-based vaccine elicits long-lasting immune protection in mice against distinct SARS-CoV-2 variants - Metzdorf, Kristin; Jacobsen, Henning; Kim, Yeonsu; Teixeira Alves, Luiz Gustavo; Kulkarni, Upasana; Brdovčak, Maja Cokarić; Materljan, Jelena; Eschke, Kathrin; Chaudhry, M. Zeeshan; Hoffmann, Markus; Bertoglio, Federico; Ruschig, Maximilian; et al. (Frontiers in Immunology, 2024)
Current vaccines against COVID-19 elicit immune responses that are overall strong but wane rapidly. As a consequence, the necessary booster shots have led to vaccine fatigue. Hence, vaccines that would provide lasting protection against COVID-19 are needed, but are still unavailable. Cytomegaloviruses (CMV) elicit lasting and uniquely strong immune responses. Used as vaccine vectors, they may be attractive tools that obviate the need for boosters. Therefore, we tested the murine CMV (MCMV) as a vaccine vector against COVID-19 in relevant preclinical models of immunization and challenge. We have previously developed a recombinant murine CMV (MCMV) vaccine vector expressing the spike protein of the ancestral SARS-CoV-2 (MCMVS). In this study, we show that the MCMVS elicits a robust and lasting protection in young and aged mice. Notably, spike-specific humoral and cellular immunity was not only maintained but even increased over a period of at least 6 months. During that time, antibody avidity continuously increased and expanded in breadth, resulting in neutralization of genetically distant variants, like Omicron BA.1. A single dose of MCMVS conferred rapid virus clearance upon challenge. Moreover, MCMVS vaccination controlled two variants of concern (VOCs), the Beta (B.1.135) and the Omicron (BA.1) variants. Thus, CMV vectors provide unique advantages over other vaccine technologies, eliciting broadly reactive and long-lasting immune responses against COVID-19.